Microstructure and polymer choice in microfluidic interfacing for nanoscale biosensing - Tijjani Adam, Shuwa; Uda, Hashim, Prof. Dr.; Mohd Faizul, Bari, Dr.; Pei, Ling Leow (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/